OPTIMIZATION OF ZAKAT MANAGEMENT IN MICRO BUSINESS EMPOWERMENT: A CASE STUDY OF BAZNAS PANGKEP REGENCY - Anwar, Muhammad; Mahsyar,; Semauin, Syahriyah; Andi Bahri,; Musmulyadi, (Jurnal Diskursus Islam, 2025)
Zakat has a strategic role in the Islamic economic system, not only as a religious obligation but also as an instrument of economic empowerment. This research was conducted to analyze the management of zakat by BAZNAS Pangkajene and Islands Regency, especially in empowering micro businesses as an effort to improve community welfare. The background of this research is the great potential of zakat in Indonesia, which is often not optimally utilized, especially in supporting micro businesses. This research uses a qualitative method with a phenomenological approach. Data were obtained through in-depth interviews with key informants, including BAZNAS managers, mustahik, and muzakki, as well as document analysis. The data collection process involved direct observation, structured interviews and literature study. Analysis was conducted inductively to explore patterns, meanings, and relevant experiences. The results showed that the management of zakat in BAZNAS Pangkajene and Islands Regency was carried out in a structured manner through the stages of planning, organizing, directing, coordinating, and supervising. This approach allows zakat to be distributed effectively and on target. Findings also show that well-managed zakat can help mustahiks develop micro-enterprises, thus contributing to their transformation into muzaki. However, challenges in community education, coordination, and supervision still require attention. The implication of this research is the need for innovation in zakat management to maximize its impact on micro business empowerment. Data-driven approach, cross-sector synergy, and integrated training program can strengthen the role of zakat as an instrument of sustainable economic development. This research provides an important contribution to the development of a more strategic and effective zakat policy.